AL-QUR’AN DAN BERBUAT BAIK (Kajian Tematik Term “Al-Birr”) - Abdullah, Dudung (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2017)
In the Qur'an there is the term al-Birr. Al-Birr means doing good orvirtue. Humans make as much effort as possible and as good as possible in doing good. Man in performing the virtue by emulatingAllah swt.